Interleukin‐10 receptor mutation presenting with severe nappy ulceration and infantile inflammatory bowel disease. (9th June 2017) - McDonald, B. S.; Narayanan, S.; Elawad, M.; Kiparissi, F.; Cullup, T.; Batta, K.
Summary: Inflammatory bowel disease (IBD) can be divided into Crohn disease, ulcerative colitis and inflammatory bowel disease unclassified (IBDU). In most patients, these disorders present in adolescence or early adulthood. Patients with infantile IBD can have an associated underlying immunodeficiency disorder caused by a mutation in interleukin (IL)‐10 or its receptor. We describe a child presenting with intractable bloody diarrhoea since 2 weeks of age and with severe nappy ulceration, who was ultimately diagnosed as having inflammatory bowel disease (IBD) due to an immunodeficiency in the IL‐10 receptor. This report highlights the importance of considering this rare immunodeficiency in patients with infantile IBD presenting with severe perianal disease to a dermatologist.